Study of the Crisis Resistance of Micro and Small Wine Companies, Markov Chain-based Analysis of their Prospects in the Aspect of the Egri Wine Region - Vincze, Judit; Antal, Sándor (Acta Carolus Robertus, 2022)
Over the past few decades, mainly in parallel with the advance of globalization and the development of the market economy in Hungary, rural economies have undergone significant changes. Their current state is characterized by a high degree of inhomogeneity and a significant degree of differentiation from both an economic and a sociological point of view. In addition to all this, however, the economic structure of each region can be linked to key sectors whose economic performance fundamentally influences the rate and direction of the development of the given region. Thus, in the case of the rural economy study of the Eger region, special attention should be paid to the wine-growing area, which, through its economic and cultural integration, can have a significant impact on the competitiveness and development of the region. The focus of our present research was on the micro and small enterprises of the Egri Borvidék wine region. During the investigation, we paid special attention to the "crisis resistance" of the enterprises in light of their economic performance after the 2008 economic crisis. We used the Markov chain model to estimate their competitiveness and development direction. Based on our results, we formulated proposals related to competitiveness and corporate stability in the aspect of micro and small companies in the wine region.
Keywords: Egri borvidék; liquidity; controlling; Markov chain model